Propagandowy obraz II Rzeszy ukazany w szacie graficznej banknotu 100 marek emisji 7 lutego 1908 roku - Markowski, Marcin (Rocznik Polsko-Niemiecki, 2014)
The bank notes which came into circulation from the turn of the nineteenth and twentieth centuries are pearls of graphic art. Using the graphic content and layout as a vehicle for the idea, each of them carries information about the country, expressed by way of commonly recognised symbols. The most extensive presentation of the Second Reich is provided in the graphic content and layout of the one hundred mark note issued on 7 February 1908, the first of three issues of that denomination. At the centre of the averse, a composition of the Prussian and imperial regalia is surrounded by a sunburst of lighter-and darker-hued rays. The averse also features two imperial eagles and the busts of two Roman deities, Mercury, the god of commerce and Ceres, the goddess of vegetation, crops and the harvest. In turn, almost the entire printed area of the reverse is taken up by a figurative scene. A personification of Germania, seated in the shade of two mighty oaks, is presented in the foreground. At her feet lie objects which allude to the German economy. The sea is depicted in the background, with three battleships sailing it in combat formation. In addition, the area designated for the watermark contains a portrait of Wilhelm I Hohenzollern. The iconography of the one hundred mark note, with its set of universal symbols, was intended to demonstrate the power of the united German Empire to the citizens of that state and foreigners alike. The images included in the graphic content and graphic composition point to the country’s real economic and military power.